New Suggestions in Sublingual Immunotherapy for House Dust Mite- Related Allergic Diseases - Ferrando, Matteo; Bagnasco, Diego; Passa-lacqua, Giovanni; Puggioni, Francesca; Varricchi, Gilda; W. Canonica, Giorgio (Current Pharmaceutical Biotechnology, 2017)
Background: The indications for Allergen immunotherapy (AIT) in patients suffering from House Dust Mite (HDM)-related allergic diseases are presently based on incomplete data. This is essentially based on the fact that HDM allergy is difficult to evaluate in clinical trials, due to the largely variable allergen exposure and symptoms, and to the long periods of observation needed to assess the effects. In addition, at variance with pollen allergy, in HDM allergy asthma is more prevalent. However, several AIT products have been approved for HDM-induced allergic rhinitis, according to their ascertained clinical efficacy, tolerability and safety profile, particularly in the sublingual form (SLIT). Objective: We reviewed herein the available data on AIT in patients with HDM-induced allergic diseases, with a particular attention to the new product MK-8237 HDM-SLIT tablets, concerning its efficacy and safety profile. Method: In the recent years, several randomized placebo-controlled clinical trials have been performed in Europe, North America and Japan to evaluate the efficacy of HDM-sublingual tablets in patients with HDM-induced allergic asthma and allergic rhinitis, mainly assessing the reduction of symptoms, exacerbations and corticosteroid intake. Results: The results of the published clinical trials were encouraging and led to the approval and commercialization of MK-8237 HDM-SLIT tablet. Conclusion: The favorable efficacy and safety profile of MK-8237 HDM-SLIT tablets provided a consolidated therapeutic option for patients with HDM-induced allergic rhinitis and asthma.
Keywords: rhinitis